Studi Biobriket Enceng Gondok (Eichhornia Crassipes) sebagai Bahan Bakar Energi Terbarukan - Eko Ariyanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Depletion of fossil energy reserves as a result of increased population growth and industrial sectors. Biomass can be considered as the best option for alternative renewable energy. The objective of this study was to investigate the possibility of water hyacinth (Eichhornia crassipes) to produce bio-briquette. The briquetting experiment was conducted with different both of tapioca strach and wood glue adhesive. The presentage of adhesive was 4%, 6%, 8%, 10%, and 12%. The briquettes were tested to evalueted water content, ash content and calorific value. The results showed that the value of water content and ash content increased by increasing presentage adhesive on bio-briquete. However, the calorific value reached the maximum point of 10 % and 8 % for addition tapioca strach and wood glue adhesive, respectively.